Attitude of Elementary School Teachers Towards the Dyslexia Students in East Kameng District of Arunachal Pradesh - Beori Yabe (Dera Natung Government College Research Journal)
This study attempts to understand the Attitude of Elementary School Teachers towards the dyslexia Students in East Kameng District of Arunachal Pradesh. It determines whether educators’ beliefs are situated negatively or positively towards the construct of dyslexia and provides insight into their conception of the disability, the perceived ‘helplessness’ of a dyslexic student and caregivers’ responses to the condition and finally, perceived barriers in terms of supporting these students. The purpose of this study is to assess the attitude of Elementary School Teachers towards the dyslexia Students. Therefore 100 teachers from 20 elementary schools were given sample of the study. The investigator also used a self-developed Likerts-5 point’s attitude scale having two sections. This scale includes 20 items (20 each for teachers) related to several dimension on attitude about dyslexia students.